Combined and isolated effects of workstation ergonomics and physiotherapy in improving cervicogenic headache and work ability in office workers: a single-blinded, randomized controlled study - Nambi, Gopal; Alghadier, Mshari; Pakkir Mohamed, Shahul Hameed; Vellaiyan, Arul; Ebrahim, Elturabi Elsayed; Sobeh, Dena Eltabey; Kashoo, Faizan Z.; Albarakati, Alaa Jameel A.; Alshahrani, Naif A.; Eswaramoorthi, Vijayamurugan (Frontiers in Public Health, 2024)
ObjectiveThe objective of the study is to compare and investigate the combined and individual effects of workstation ergonomics, physiotherapy and patient education in improving CgH headaches and work ability in office workers.Methods96 eligible CgH participants were divided into the ergonomics modifications group (EMG; n = 24), physiotherapy group (PTG; n = 24), and ergonomics modifications combined with physiotherapy group (EPG; n = 24) and education control group (CNG; n = 24), the participants received the respective treatment for 4 weeks. Primary (CgH frequency) and secondary (CgH pain intensity, CgH disability, flexion rotation test (right and left), neck disability index and work ability) scores were measured. The effects of treatment at various intervals were analyzed with a 4 × 4 linear mixed model analysis (LMM) between treatment groups and time intervals.ResultsFour weeks following training EPG group showed more significant changes in primary outcome CgH frequency; 4.6 CI 95% 3.63 to 5.56 when compare to control group. The same gradual improvement was noticed at 8 weeks 8.2 CI 95% 7.53 to 8.86 and at 6 months follow up 11.9 CI 95% 11.25 to 12.54 when compare to other groups (p = 0.001) which is statistically 52.97% improvement. Similar improvements can be seen in the secondary outcome measures such as CgH pain intensity, CgH disability, flexion rotation test (right and left), neck disability index and work ability in EPG group than the EMG, PTG, and CNG groups (p = 0.001) at 4 weeks, 8 weeks and at 6 months’ follow-up.ConclusionThis study observed that the workstation ergonomics and physiotherapy group experienced significantly more improvements in cervicogenic headache patients.Clinical trial registrationIdentifier NCT05827185